Alterations in cell mechanics by actin cytoskeletal changes correlate with strain-specific rubella virus phenotypes for cell migration and induction of apoptosis - Kraeter, Martin; Sapudom, Jiranuwat; Bilz, Nicole Christin; Pompe, Tilo; Guck, Jochen; Claus, Claudia (Cells, 2018)
The cellular cytoskeleton is central for key cellular functions, and as such is a marker for diseased and infected cell states. Here we analyzed infection with rubella virus (RV) strains with respect to phenotypes in cellular mechanical properties, cell movement, and viral cytopathogenicity. Real-time deformability cytometry (RT-DC), as a high-throughput platform for the assessment of cell mechanics, revealed a correlation of an increase in cortical filamentous-actin (F-actin) with a higher cellular stiffness. The additional reduction of stress fibers noted for only some RV strains as the most severe actin rearrangement lowered cell stiffness. Furthermore, a reduced collective and single cell migration speed in a wound healing assay was detected in addition to severe changes in cell morphology. The latter was followed by activation of caspase 3/7 as a sign for induction of apoptosis. Our study emphasizes RT-DC technology as a sensitive means to characterize viral cell populations and to implicate alterations of cell mechanical properties with cell functions. These interdependent events are not only promising options to elucidate viral spread and to understand viral pathologies within the infected host. They also contribute to any diseased cell state, as exemplified by RV as a representative agent for cytoskeletal alterations involved in a cytopathological outcome.
CRIS-Team Scopus Importer:2022-08-05
Keywords: Actin stress fibers; Cell stiffness; Cytochalasin D; Gap closure assay; Real-time deformability cytometry; Single cell tracking; Wound healing